Attitudes toward Total Physical Response and the Natural approach - Kademlija Dedic; Senad Bećirović (International Journal of Education and Humanities, 2021)
This paper explores the difference between teaching methods and critical assessment of teaching methods in the educational process. Total Physical Response (further TPR) and Natural approach will be reviewed. The literature review results will help to notice the differences between these methods when it comes to teaching/learning processes that are in use today. Choosing an appropriate method to teach is way more complicated. But the common thing for all students is the goal of their learning, which is to adopt the foreign language. Students need to have a desire to learn, the purpose of their learning process, and additionally, they need to have the opportunity to speak and fully develop speaking abilities. The current study findings may conclude what method will make students acquire a target language and how they will adopt it even if they are early beginners. The paper focuses on the descriptive method according to the previous findings among works of other researchers. The paper concludes that Total Physical Response has a positive impact. It brings a desire for learning because of its method for building a happy classroom environment. At the same time, the Natural Approach enhances the students to express their opinion and feelings freely. Total Physical Response is common at a very early stage of a learning process, while the Natural Approach can be used among students who want to improve their speaking abilities in a positive and natural environment